Critical Review of Workload Distribution between Nurses and Health Assistants in Healthcare Settings - Alrowili , Areeg Jaza; Alkhaial , Talal Mohammed F; Alsharari , Khalaf Sabah M; Alsharari, Yaser Madallah B; Alshreya , Hussein Mohammed H; Alshareya, Msfer Mohammad H; Alrwilan , Rakan Ali M; Alsharari , Hani Dhaher; Al-Sharari, Abdulaziz Hamed S; Al-Sharari , Khairallah Awad; Alsallum , Abdullah Hadi M; Lasloum, Meteb Saleh A; et al. (Journal of Ecohumanism, 2024)
The equitable distribution of work among the nurses and health assistants is essential to maintaining the optimum quality of patient care, staff contentedness, and effectiveness of the different health facilities. Unequal distribution of tasks affects the level of emotionally and physically burned-out nurses who lack job satisfaction and provide substandard services. At the same time, the health assistants are overtrained, yet their skills are underemployed. Dependence on gender and other factors to assign certain tasks results in disadvantages for the healthcare professionals in addition to negatively affecting patient care with worse prognosis and potential for mistakes. The gaps reveal that while nurses perform clinical and administrative work and have little face-to-face time with the patient, health assistants are locked into non-clinical work despite their capabilities. The following critical review assesses the current status of workload issues and key findings regarding its influence on health care and workforce concerns. Thus, reviewing the recent research defines the major issues like role conflict and enrichment, lack of effective policies, and organizational resistance to change. The review also points out that there is a need for developing substantial system improvements to improve the textual roles, such as there should be proper demarcation of roles, training that increases the competencies of Health assistants, as well as the incorporation of technology inventions such as task management systems, among others. Such interventions can enhance the fairness of workload distribution, decrease staff turnover, and enhance resource management, promoting efficiency and teamwork. Resolution of these problems is crucial to maintaining high standards of patient care and promoting healthcare employees’ welfare, therefore establishing international collaboration as urgent in managing healthcare professionals’ workloads.